1992
DOI: 10.1002/gcc.2870040207
|View full text |Cite
|
Sign up to set email alerts
|

Chromosomal abnormalities in skin following total body or total lymphoid irradiation

Abstract: Patients undergoing bone marrow transplantation often receive total body or total lymphoid irradiation as part of the conditioning regimen prior to marrow infusion. The cytogenetic effects of this therapy on skin fibroblasts were studied. Fibroblast cultures from eight skin biopsies were harvested in early passages for G-banded chromosome analysis. Four biopsies were from three patients who had high-dose cyclophosphamide and total body radiotherapy; one was from within and one was from outside the radiation fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

1994
1994
2015
2015

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 31 publications
0
4
0
Order By: Relevance
“…It is unlikely, that all these aberrations developed ex vivo in culture, because most skin metaphases were normal before SCT. In the literature there is only one small series of four pediatric patients after TBI or total lymphoid irradiation, where authors found 49 to 88 % aberrant metaphases in the skin biopsies taken within radiotherapy fields [ 19 ]. A few case reports have also been published describing chromosomal aberrations in skin fibroblasts after in vivo radiation exposure [ 15 – 18 , 25 ], but without comparison to pre-radiation metaphases.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…It is unlikely, that all these aberrations developed ex vivo in culture, because most skin metaphases were normal before SCT. In the literature there is only one small series of four pediatric patients after TBI or total lymphoid irradiation, where authors found 49 to 88 % aberrant metaphases in the skin biopsies taken within radiotherapy fields [ 19 ]. A few case reports have also been published describing chromosomal aberrations in skin fibroblasts after in vivo radiation exposure [ 15 – 18 , 25 ], but without comparison to pre-radiation metaphases.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore it cannot be excluded that the extent of the observed cytogenetic damage in the present study may have been influenced in part by radiation enhancing effects of chemotherapy. However in a small series of SCT-patients, abnormal karyotypes were only observed in those with TBI, but not in those without [ 19 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations